THE EFFECTIVENESS OF STORY WITH TEN PICTURES GAME TO DEVELOP GRADE O STUDENTSâ€™ ABILITY IN TELLING STORY - Winanto, Ardiyanus; Sudarsono, Sudarsono; Rosnij, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to examine the effectiveness of story with ten pictures game to develop Grade O students ability in telling story. This research was conducted to Grade O students of Kampoeng English Poernama in Academic Year of 2017 by administering a speaking performance test before and after the treatment. It was a pre-experimental design. The population of this research was all students of Kampoeng English Poernama in Academic Year of 2017, and the sample was taken from Grade O which consisted of 12 students. The data were analyzed by using t-test and effect size formula. The findings showed that the ten pictures game is significantly effective to develop studentsâ€™ ability in telling story. Therefore, the alternative hypothesis which stated â€œStory with ten pictures game is effective to develop grade O studentsâ€™ ability in telling storyâ€ is accepted.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Key words: Story with Ten Picures Game, Telling Story, Pre Experimental Study